Students Mathematic Problem Solving Process in Two Variable Linear Equation Systems from Cognitive Field Dependent Style - Nuraida, Nuraida; Aripin, Usman; Pereira, Jerito (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to describe the process of solving mathematical problems in the subjects of a two-variable linear equation system in terms of field-dependent cognitive style. The type of research used is descriptive qualitative research. The research subjects were 15 grade VIII students in one of the public junior high schools in Cimahi City. In this study, the instrument used was a problem-solving test consisting of 2 questions on the material of a two-variable linear equation system and interviews for 3 students with field dependent cognitive style. The results showed that the steps of solving mathematical problems of students with cognitive style field dependent were categorized as good at the stage of understanding the problem and re-examining, categorized enough at the stage of planning completion, and categorized less at the stage of implementing the completion plan. This means, if field dependent students can understand the problem or problem, it will affect the next step.